'The Invisible Reality Show': Performative intervention and the production of the contemporary space. Issue 2 (8th December 2011) - GOMES, FERNANDA
The performance intentions that interfene into public spaces− 'site-specific performances' – can raise several issues, and this article will debate some of them. From artistic, sociological, cultural and geographic perspectives, urban interventions and performances take place in the artistic scenario and in the development of contemporary space. This article starts with the experience of the Danish group 'Udflugt', that has been in Rio de Janeiro presenting the methodologies and processes which arose after the birth of the concept of 'The Invisible Reality Show' which is used in their work. Through this article I intend to make connections between the perceptive changes of daily space, the processes of sociability, and the artistic experience in the urban context.